2012
DOI: 10.1007/s10853-012-6531-y
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the compound middle lamella in spruce latewood by micro-pillar compression of double cell walls

Abstract: The mechanical integrity of the interface between two adjacent cells in spruce late wood was studied by uniaxial compression of focused ion beam machined micro-pillars of double cell walls (DCW) containing the compound middle lamella (CML). The DCW reveals a lower yield strength and stiffness than the secondary cell wall (S2). Failure occurs by tearing of the interface between the first (S1) and second layers (S2) of the secondary cell wall exposing the internal arrangement of the microfibrils, while the CML r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In addition, the images collected confirm the observations done by Zamil and Geitmann [13] and Raghavan et al [15] in the ML and S 1 -S 2 region. The authors reported that the middle lamella is stronger than the primary or secondary wall layers and not damaged from a mechanical stretch; on the contrary, fractures take place in the adjacent primary or secondary cell-wall layers.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the images collected confirm the observations done by Zamil and Geitmann [13] and Raghavan et al [15] in the ML and S 1 -S 2 region. The authors reported that the middle lamella is stronger than the primary or secondary wall layers and not damaged from a mechanical stretch; on the contrary, fractures take place in the adjacent primary or secondary cell-wall layers.…”
Section: Resultssupporting
confidence: 88%
“…Between the fibers, there is another layer called middle lamella (ML), which cements the primary cell walls of adjacent cells together and is mainly composed of pectic polysaccharides, lignin, and a small amount of proteins [12][13][14]. This binder layer between two cells acts as a very thin and efficient interfacial matrix in the plant [13,15].…”
mentioning
confidence: 99%
“…The failure occurred either at the S 3 layer or in the ML (see Supplementary Figure S3). This represents a different failure mechanism from the one observed in Raghavan et al (2012) that consisted of a tearing of the interface between the S 1 and the S 2 layers of the CW.…”
Section: Resultsmentioning
confidence: 69%
“…As seen from Table 1, the average yield stress provided by MCo (183 ± 11.9 MPa) was higher than the values in the cited literature. For instance, Raghavan et al (2012) obtained a yield strength of about 125 ± 20 MPa and Adusumalli et al (2010) obtained 158 ± 20 MPa from five micropillars, both investigated for spruce latewood. The obtained higher strength and yield stress can be attributed to the fact that a species different from that in mentioned literature was measured and, moreover, to the fact that libriform fibers in late wood zone were measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation